STRATEGI PENYELESAIAN KONFLIK TANAH PERKEBUNAN - Ktut Diara Astawa (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: Land has important position and function for everyone, especially to achieve life prosperity.Claiming rights over a land usually go with different perception of more than one party involvedwhich cause conflict. This research tries to reveal and describe factors of the conflict, parties thatinvolve, strategy to solve the conflict, and the solution. Research shows us that there are so manyfactors, so many ways to solve the conflict, and big state role in conflict resolution making process.Keywords : conflict, state role, plantation